Enterochromaffin cells in the duodenal mucosa of children with coeliac disease. - Challacombe, D N (1977)
A cell counting technique was used to count enterochromaffin (EC) cells in the duodenal mucosa of 10 children with coeliac disease and 10 controls, and significantly greater numbers of EC cells were found in children with coeliac disease. In four children with a clinical history suggestive of coeliac disease, but with minor histopathological changes in the duodenum, gluten challenge resulted in increased numbers of EC cells. Abnormalities of 5-hydroxytryptamine metabolism in coeliac disease may result from hyperplasia of EC cells in the small intestine.